Effect of reinforcements in chip forming mechanisms of discontinuous natural fiber composites while milling. (April 2022) - John, Raveen; Lin, Richard; Jayaraman, Krishnan; Bhattacharyya, Debes
Abstract: Machining discontinuous natural fiber-reinforced composites (NFRCs) has been vitally challenging, mainly because of surface quality issues. Therefore, for the first time, an investigation to gain the phenomenological perspective of fundamental material removal mechanisms has been undertaken for two remarkably distinct polypropylene (PP) composites reinforced by rice husk (RH) and kenaf. In-situ side-end milling experiments have been performed employing a high-speed camera at different cutting speeds. The morphology of chip roots attained by a quick stop procedure along with chips is examined by scanning electron microscopy. The paper analyzes the distinct critical transitions in cutting mechanisms and cracking patterns along with chip reduction coefficients (ζ), shear angles (Ø), tool-chip temperatures, and friction coefficients (μ) influenced by the diverse reinforcement characteristics and cutting conditions. At low speeds, compared to kenaf/PP composites, RH/PP being less ductile with harder, more abrasive and larger width RH revealed reasonably defective slot side-wall surface, characterized by a cut through and dislodgement of RH. Graphical abstract: Image 1 Highlights: The effect of reinforcements and cutting speeds on material removal mechanism of discontinuous natural fiber-reinforced composites is examined. In-situ high-speed camera and scanning electron microscopic observations are used to characterize the fundamental difference in chip formation. Different cutting mechanisms through varied cracking patterns and deformation are interpreted. Shear angles, friction coefficients, chip reduction coefficients, temperatures, morphological surface finishes and chips are analyzed.